2015
DOI: 10.1007/s10620-014-3471-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Health-Related Quality of Life and Adherence in Crohn’s Disease and Ulcerative Colitis: Implications for Clinical Management

Abstract: Among patients with IBD, a higher level of perceived stress is a strong predictor of lower HRQOL and lower adherence to provider recommendations. Additionally, females with CD and patients with higher number of IBD relapses may be at risk of lower HRQOL. Psychological interventions, including physician-facilitated conversations, psychological screeners, and a multidisciplinary approach, may help address impaired HRQOL and adherence and merit further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 44 publications
4
46
1
3
Order By: Relevance
“…Women reporting lower HRQOL at pre-operative baseline and in the short-term postoperative period are consistent with studies evaluating predictors of HRQOL in CD patients in general [8,41,42] . However, the similar HRQOL reported by men and women by 18 months after surgery may suggest that postoperative HRQOL is better explained by other factors such as smoking or disease recurrence.…”
Section: Summary Of Main Findings and Interpretationsupporting
confidence: 82%
“…Women reporting lower HRQOL at pre-operative baseline and in the short-term postoperative period are consistent with studies evaluating predictors of HRQOL in CD patients in general [8,41,42] . However, the similar HRQOL reported by men and women by 18 months after surgery may suggest that postoperative HRQOL is better explained by other factors such as smoking or disease recurrence.…”
Section: Summary Of Main Findings and Interpretationsupporting
confidence: 82%
“…Quality of life (QOL) was the most common outcome of interest, however depression, anxiety, psychological distress and perceptions of disability were also studied. Only three studies reported findings separately for ulcerative colitis and Crohn's disease (Boye et al, 2008, Goodhand et al, 2012, Tabibian et al, 2015. All other studies, on finding no significant differences performed their statistical analysis on the group as a whole.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Dentro de ellos destacan pacientes mujeres, que presenten un mayor grado de estrés, menor apoyo social, un mayor número de recaídas de su enfermedad, síntomas persistentes después de 10 años de seguimiento y una pensión de invalidez por EII 31,32 . La EC es una enfermedad heterogénea que puede presentar tres fenotipos distintos (inflamatorio, penetrante y fistulizante), los cuales resultan de una compleja interacción entre factores genéticos, inmunológicos y ambientales.…”
Section: Discapacidadunclassified
“…Los instrumentos clásicos para medir calidad de vida son el SF-36 y el SF-12, los cuales se han utilizado en algunos estudios en EII 32,36,37 , pero no son específicos para esta patología. El instrumento más comúnmente utilizado en la práctica clínica y en los estudios es el IBDQ 31,[32][33][34][35][36]38 desarrollado en la Universidad de McMaster, Ontario, Canadá, el cual consta de 32 preguntas 39 . Este cuestionario se encuentra traducido y validado al español 38 .…”
Section: Discapacidadunclassified
See 1 more Smart Citation